Guidance Note on IMF Engagement on Social Safeguards in Low-Income Countries. (Policy Papers; Policy Paper, 2018)
This note provides operational guidance to staff on how to engage on social safeguard issues with low-income countries in both program and surveillance contexts. The note is not intended as a comprehensive guide, and should be used in conjunction with other operational guidance notes, such as those relating to conditionality and surveillance.